Analisis Peran Hukum dan Ekonomi Makro Terhadap Inflasi Kota Bandung Tahun 2020 - Dwi Ratna Kartikawati (Fakultas Hukum Universitas Islam Batik Surakarta, 2023)
This writing aims to analyze the role of law in regulating economic policies in the city of Bandung in suppressing the inflation rate. The approach used in this writing is a qualitative descriptive approach with data collection techniques through secondary data literature studies. The results of a literature study show that inflation in the city of Bandung in 2020 reached 6.04%. Factors contributing to this inflation were rising fuel prices, the rainy season which resulted in rising vegetable prices, and the COVID-19 pandemic which had an impact on market uncertainty. From a macroeconomic perspective, the role of law is very important in regulating economic policies to suppress inflation. In the city of Bandung, policies implemented include controlling the prices of goods, expanding micro, small and medium enterprises (MSMEs), and monitoring monetary policy. Therefore, proper application of laws and regulations is needed to create economic stability in the city of Bandung and Indonesia in general. Keywords: Inflation, Law, Macroeconomics.